Know Your Audience - Whitney A. Cesari; Sumeet S. Vaikunth; Jim B. Lewis; Mukta Panda (SAGE Publishing, 2012)
Purpose: To identify the chief complaints and demographics at Clinica Esperanza, a student-run free clinic for an underserved Hispanic population. Methods: A retrospective chart review of patient files from 2005 through 2010 was undertaken, as approved by the University of Tennessee Health Science Center's Institutional Review Board. Results: From 2005 through 2010, Clinica Esperanza fielded 2551 patient visits, consisting of 951 unique patients, 609 females and 342 males. Mean age was 34 years, and 60% of patients presented once, while 13% followed up for 1 year, 9% for 2 years, 6% for 3, 6% for 4, and 4% for 5. "Pap smear," "abdominal pain," and "follow-up lab results" ranked, in order, as the 3 top chief complaints. Discussion: Resulting data have led to several improvements. The clinic has remained open weekly to improve patient continuity. With the top 10 chief complaints identified, they are better addressed. More funding is allocated for speculums and proper training of Pap smear technique. Systematic reporting of lab results is being implemented. Physical therapists and pharmacists now participate to address musculoskeletal and medication-based needs, respectively. A volunteer gastroenterologist has been recruited to provide specialized care for abdominal pain. An electrocardiogram machine is now used to evaluate chest pain. To improve student-patient communication, online language learning modules have been created. Conclusions: Based on these data, improvements in health care services have been made, including better continuity, emphasis on top chief complaints, and provider education in medical Spanish. Future plans include on-site pharmacy, smoother referrals, and similar clinics on the University of Tennessee Health Science Center's other campuses.